A catalyst for fuel cells, its preparation method and use
Patent Information
- Application Number
- CN202210983008.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-16
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-08-16
AI Technical Summary
[0004]为了解决现有技术存在的上述不足,本发明的目的是提供一种燃料电池用催化剂及其制备方法和应用,以解决现有燃料电池用催化剂制备过程碳载体容易团聚、贵金属在碳载体上搭载量低以及不适合大规模生产的问题
[0027] This invention utilizes anionic porous resin to adsorb metals, thereby increasing the loading capacity of active metals and enhancing the loading stability of metal ions. Furthermore, the carbon support formed after heat treatment of the porous resin has high porosity and a large specific surface area, which not only allows for the loading of more active metals but also increases the number of channels for reactants to diffuse into the catalyst layer, significantly reducing the amount of catalyst required and thus lowering the production cost of fuel cells.
Smart Images

Figure HDA0003800960820000011 
Figure HDA0003800960820000021 
Figure HDA0003800960820000022
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fuel cell technology, specifically relating to a fuel cell catalyst, its preparation method, and its application. Background Technology
[0002] Fuel cells are characterized by high efficiency, environmental friendliness, cleanliness, and high energy density. One of the main factors affecting fuel cell performance is the activity of the catalyst. Developing highly active catalysts is key to reducing catalyst usage and lowering fuel cell costs.
[0003] Carbon, used as a catalyst support material in fuel cells, typically employs materials such as carbon black and carbon nanotubes. Existing carbon supports are mostly solid structures, often resulting in insufficient exposure of the metal catalyst. In particular, the uneven surface of the carbon catalyst prevents the utilization of precious metal catalysts confined within its recesses. Secondly, traditional carbon supports have weak anchoring effects on adsorbed and precipitated metal salt precursors on their surfaces. During high-temperature reduction heat treatment, the reduced metal nanoparticles are prone to sintering, agglomeration, and growth, thereby reducing the catalyst's active area and catalytic activity. Furthermore, the lack of functional groups on the surface of existing carbon supports makes them difficult to disperse or prone to agglomeration, hindering the mounting of precious metals and resulting in lower activity in the final product due to insufficient precious metal loading. Summary of the Invention
[0004] In order to overcome the above-mentioned shortcomings of the existing technology, the purpose of this invention is to provide a catalyst for fuel cells, its preparation method and application, so as to solve the problems of easy agglomeration of carbon support, low loading of precious metals on carbon support and unsuitability for large-scale production in the preparation process of existing fuel cell catalysts.
[0005] The technical solution of the present invention to solve the above-mentioned technical problems is as follows:
[0006] A method for preparing a catalyst for a fuel cell includes the following steps:
[0007] (1) Dissolve the Pt precursor and the soluble metal precursor in water, then add an anion exchange resin for adsorption, then separate and dry to obtain a resin adsorbed with metal ions.
[0008] (2) The resin adsorbed with metal ions is dispersed in a solvent, and then a silicon-containing compound hydrolyzed under acidic or alkaline conditions is added. Then, an acid solution or an alkaline solution is added for hydrolysis, and the hydrolysate coats the resin adsorbed with metal ions.
[0009] (3) The material obtained in step (2) is heat-treated in a reducing atmosphere, and then the heat-treated material is post-treated, washed and dried to obtain the final product.
[0010] The beneficial effects of this invention are as follows: In preparing the catalyst, the Pt precursor and a soluble metal precursor are first co-dissolved in water, and then an anionic porous resin is added. The metal cations are adsorbed by the anionic porous resin, thus achieving the purpose of loading the metal cations onto the support. This invention uses anionic porous resin as the adsorption support for metal ions. During subsequent heat treatment, it forms porous nitrogen-doped carbon. Compared to the solid carbon supports widely used in existing technologies, the carbon support obtained by this invention has a hollow structure, higher porosity, and a larger specific surface area. This not only allows for the loading of more active metals but also increases the number of channels for reactants to diffuse into the catalyst layer, significantly reducing the amount of catalyst used and thus lowering the production cost of fuel cells.
[0011] In this invention, after the resin adsorbs metal ions, the resin containing adsorbed metal ions is further coated with a silicon-containing compound. The coating not only further improves the adsorption stability of metal ions, but more importantly, the metal nanoparticles loaded on the coated resin are less likely to agglomerate during heat treatment. In addition, volatile substances such as water are also coated in the coating process. During the subsequent heat treatment, the volatile substances volatilize, providing a certain growth space for the catalyst, thereby controlling the particle size of the catalyst.
[0012] Furthermore, the particle size of the anion exchange resin is below 0.25 mm.
[0013] The beneficial effects of the above-mentioned further technical solutions are as follows: controlling the particle size of the anionic porous resin can not only increase the specific surface area of the adsorption resin and improve the loading of metal ions, but also regulate the size of the final catalyst.
[0014] Furthermore, in step (1), the molar ratio of Pt precursor to soluble metal precursor is 1:1 to 5:1.
[0015] Furthermore, the Pt precursor is chloroplatinic acid, potassium chloroplatinate, or potassium chloroplatinate; the soluble metal precursor is at least one of sodium cobalt cyanide, potassium cobalt cyanide, ammonium hexachlororuthenate, potassium pentachlororuthenate, potassium hexacyanoruthenate, ammonium molybdate, sodium molybdate, chloroauric acid, sodium ferrocyanide, potassium ferrocyanide, potassium nickel cyanide, potassium hexacyanide nickelate, potassium chloropalladium, sodium chloropalladium, ammonium chloropalladium, sodium tungstate, ammonium tungstate, sodium stannate, and potassium stannate; the anion exchange resin is MP62, D301 resin, etc.
[0016] Furthermore, in step (1), the adsorption temperature is 15–80℃ and the adsorption time is 4–12h.
[0017] Furthermore, the mass ratio of the silicon-containing compound (calculated as silicon dioxide) to the resin adsorbed with metal ions is 1:2 to 2:1.
[0018] Furthermore, the silicon-containing compound is a silicate, methyl orthosilicate, ethyl orthosilicate, or 3-aminopropyltriethoxysilane.
[0019] Furthermore, the acid solution is a hydrochloric acid solution with a pH of 1 to 3, and the alkaline solution is an ammonia solution with a pH of 9 to 11.
[0020] Furthermore, in step (2), the hydrolysis temperature is 15–80℃ and the hydrolysis time is 3–10h.
[0021] Furthermore, the reducing atmosphere is a mixture of hydrogen and argon or hydrogen and nitrogen, wherein the volume content of hydrogen in the mixture is 5% to 40%.
[0022] Furthermore, in step (3), the heat treatment temperature is 700–900℃ and the heat treatment time is 6–8h.
[0023] Further, in step (3), the post-treatment involves immersing the heat-treated material in a 1-3M sodium hydroxide solution at 80-120°C for 50-70 hours, followed by acid washing with a 1-3M nitric acid solution at 50-70°C for 2 hours; or immersing the heat-treated material in a 10% hydrofluoric acid solution and stirring at room temperature for 5-12 hours; or immersing the heat-treated material in a mixed solution of glacial acetic acid, hydrofluoric acid, and ammonium fluoride and stirring at room temperature for 1-8 hours, wherein the volume ratio of glacial acetic acid, hydrofluoric acid, and ammonium fluoride in the mixed solution is 4:1:7.
[0024] This invention also discloses a catalyst for fuel cells, which is prepared using the method described above. The fuel cell catalyst of this invention can be represented as: PtCo / C, PtFe / C, PtNi / C, PtPd / C, PtCoAu / C, PtPdAu / C, PtRu / C, PtRuCo / C, PtSnCo / C, Pt-MoC / C, or PtRu-MoC / C.
[0025] This invention also discloses the application of catalysts for fuel cells, which can be used as oxygen reduction catalysts for fuel cell cathodes, hydrogen hydroxide catalysts for fuel cells, or anode catalysts for methanol fuel cells.
[0026] The present invention has the following beneficial effects:
[0027] This invention utilizes anionic porous resin to adsorb metals, thereby increasing the loading capacity of active metals and enhancing the loading stability of metal ions. Furthermore, the carbon support formed after heat treatment of the porous resin has high porosity and a large specific surface area, which not only allows for the loading of more active metals but also increases the number of channels for reactants to diffuse into the catalyst layer, significantly reducing the amount of catalyst required and thus lowering the production cost of fuel cells.
[0028] This invention, through the coating of silicon-containing compounds, avoids the sintering and agglomeration of metal ions while allowing for the control of catalyst size, thus achieving the goal of adjustable catalyst size. Attached Figure Description
[0029] Figure 1 The results are the performance test results of the PtCo / C catalyst prepared in Example 1.
[0030] Figure 2 The results are the performance test results of the PtCo / C catalyst prepared in Example 2.
[0031] Figure 3 The results are the performance test results of the PtNi / C catalyst prepared in Example 3.
[0032] Figure 4 The results are the performance test results of the catalyst PtRuMo / C prepared in Example 4.
[0033] Figure 5 The results are the performance test results of the catalyst PtRuCo / C prepared in Example 5.
[0034] Figure 6 The results are the performance test results of the PtFe / C catalyst prepared in Example 6.
[0035] Figure 7 The results are the performance test results of the PtSnCo / C catalyst prepared in Example 7.
[0036] Figure 8 The results are the performance test results of the PtCoAu / C catalyst prepared in Example 8.
[0037] Figure 9 The results are the performance test results of the PtPdAu / C catalyst prepared in Example 9.
[0038] Figure 10 The results are the performance test results of the PtPd / C catalyst prepared in Example 10.
[0039] Figure 11 The results are the performance test results of the catalyst PtRuFe / C prepared in Example 11.
[0040] Figure 12 The results are the performance test results of the catalyst PtRuMoNi / C prepared in Example 12.
[0041] Figure 13 The results are the performance test results of the PtRuNi / C catalyst prepared in Example 13.
[0042] Figure 14The results are the performance test results of the PtMo / C catalyst prepared in Example 14. Detailed Implementation
[0043] The examples given below are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified, conditions in the examples are performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0044] The anion exchange resins used in this invention include MP62 and D301 resins.
[0045] The electrochemical performance testing conditions for the obtained catalyst in this invention are as follows:
[0046] CV: CV curve of N2-saturated 0.1M HClO4 solution, scan rate 50 mV / s -1 ;
[0047] LSV: LSV curve in O2-saturated 0.1M HClO4 solution, scan rate 10 mV / s -1 1600 rpm;
[0048] CO: 0.1M N2 saturated HClO4 solution at 10mV s -1 The scan rate is used to record CO removal.
[0049] Example 1: PtCo / C catalyst
[0050] A PtCo / C catalyst for fuel cells is prepared by the following steps:
[0051] (1) Take MP62 resin and grind it through a 60-mesh sieve (0.25mm);
[0052] (2) Take 1g of ground MP62 resin, add an appropriate amount of ultrapure water to prepare a solution of 0.1g / mL, then add 5.6mL H2PtCl6 and 0.1821g K3[Co(CN)6] in sequence, stir and mix evenly, adsorb at room temperature for 4h, then centrifuge and dry to obtain resin adsorbed with metal ions.
[0053] (3) Disperse the resin adsorbed with metal ions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silica, the silica generated after hydrolysis) to the resin adsorbed with metal ions is 1:1. Then add an equal volume of pH=1 HCl solution, pour into a petri dish, and hydrolyze at room temperature for 6 hours. The hydrolysate coats the resin adsorbed with metal ions.
[0054] (4) The product obtained in step (3) is heat-treated in a mixture of hydrogen and nitrogen, wherein the volume content of hydrogen in the mixture is 5%, the heat treatment temperature is 800℃, and the time is 6.5h.
[0055] (5) The heat-treated material is immersed in 2M NaOH solution and hydrothermally treated at 80℃ for 60h. Then it is acid washed with 1M HNO3 solution at 60℃ for 2h. After filtration, washing, drying and grinding, the desired catalyst is obtained.
[0056] The performance test results of the catalyst obtained in Example 1 are as follows: Figure 1 As shown, 1-1 is the XRD detection result, 1-2 is the LSV detection result, 1-3 is the CO dissolution detection result, 1-4 is the single cell polarization curve and power density curve, and 1-5 is the TEM image and mapping image.
[0057] XRD analysis showed that the diffraction peaks corresponded one-to-one with the standard Pt3Co card, indicating that the synthesized PtCo / C catalyst is an ordered intermetallic compound with a wide half-peak width, small catalyst particles, strong diffraction peaks, and good alloying properties. LSV: The half-wave potential shifted positively by 19 mV compared to JM-Pt / C, indicating that silica can inhibit sintering and improve catalyst activity. TEM showed that the catalyst was uniformly dispersed on the carbon support with only slight agglomeration and small particle size, consistent with XRD. Mapping showed uniform elemental distribution. Fuel test results showed that PtCo / C outperformed JM-Pt / C.
[0058] Example 2: PtCo / C catalyst
[0059] A PtCo / C catalyst for fuel cells is prepared by the following steps:
[0060] (1) Take MP62 resin and grind it through a 60-mesh sieve (0.25mm);
[0061] (2) Take 1g of ground MP62 resin, add an appropriate amount of ultrapure water to prepare a solution of 0.1g / mL, then add 5.6mL H2PtCl6 and 0.1556g Na3[Co(CN)6] in sequence, stir and mix evenly, adsorb at 30℃ for 6h, then centrifuge and dry to obtain resin adsorbed with metal ions.
[0062] (3) Disperse the resin adsorbed with metal ions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 0.65:1. Then add an equal volume of pH=10NH3·H2O solution and stir at 60℃ for 3h to hydrolyze. The hydrolysate coats the resin adsorbed with metal ions.
[0063] (4) The product obtained in step (3) is heat-treated in a mixed gas of hydrogen and nitrogen, wherein the volume content of hydrogen in the mixed gas is 20%, the heat treatment temperature is 800℃, and the time is 6.5h.
[0064] (5) The heat-treated material is immersed in a 10% HF solution and stirred at room temperature for 10 hours. Then, it is filtered, washed, dried and ground to obtain the desired catalyst.
[0065] The performance test results of the catalyst obtained in Example 2 are as follows: Figure 2 As shown, 2-1 is the XRD detection result and 2-2 is the LSV detection result.
[0066] XRD analysis confirmed the successful synthesis of an ordered PtCo / C catalyst, with oxygen reduction polarization curves showing a half-wave potential 23 mV higher than that of JM-Pt / C. Changing the precursor metal ions had no significant effect on the synthesized catalyst. LSV curves showed a 23 mV positive shift in the PtCo / C catalyst compared to the JM-Pt / C catalyst; the enhanced activity is likely due to Co altering the electronic structure of Pt. This indicates that hydrolysis of tetraethyl orthosilicate under acidic and alkaline conditions has little effect on the catalyst's protective effect.
[0067] Example 3: PtNi / C catalyst
[0068] A PtNi / C catalyst for fuel cells is prepared by the following steps:
[0069] (1) Take D301 resin and grind it through a 60-mesh sieve (0.25mm);
[0070] (2) Take 1g of ground D301 resin, add an appropriate amount of ultrapure water to prepare a solution of 0.1g / mL, then add 6.57mL H2PtCl6 and 0.154g K2Ni(CN)4 in sequence, stir and mix evenly, adsorb at 40℃ for 8h, then centrifuge and dry to obtain resin adsorbed with metal ions.
[0071] (3) Disperse the resin adsorbed with metal ions in ethanol solvent, then add sodium silicate. The mass ratio of the added sodium silicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 0.6:1. Then add an equal volume of pH=10NH3·H2O solution and stir at 60℃ for 8 hours to hydrolyze. The hydrolysate coats the resin adsorbed with metal ions.
[0072] (4) The product obtained in step (3) is heat-treated in a mixed gas of hydrogen and nitrogen, wherein the volume content of hydrogen in the mixed gas is 10%, the heat treatment temperature is 900℃, and the time is 8h.
[0073] (5) The heat-treated material is immersed in 2M NaOH solution and hydrothermally treated at 80℃ for 60h. Then, it is filtered, washed, dried and ground to obtain the desired catalyst.
[0074] The performance test results of the catalyst obtained in Example 3 are as follows: Figure 3 As shown, 3-1 is the XRD detection result, 3-2 is the LSV detection result, 3-3 is the CO dissolution detection result, and 3-4 is the TEM image and mapping image.
[0075] XRD analysis showed that the diffraction peak positions of the PtNi / C alloy catalyst corresponded to those of the Pt standard card, and the main peaks of PtNi / C shifted to higher angles, indicating the successful synthesis of the PtNi / C alloy catalyst. The half-wave potential was 28 mV higher than that of JM-Pt / C, and the calculated ECSA based on CO dissolution was 67.52 mV. 2 / g, higher than JM-Pt / C. TEM showed that the alloy catalyst was uniformly dispersed on the support, and the mapping pattern showed that Pt and Ni elements were uniformly dispersed in the alloy particles of the support.
[0076] Example 4: PtRuMo / C catalyst
[0077] A PtRuMo / C catalyst for fuel cells is prepared by the following steps:
[0078] (1) Take D301 resin and grind it through a 60-mesh sieve (0.25mm);
[0079] (2) Take 1g of ground D301 resin, add an appropriate amount of ultrapure water to prepare a 0.1g / mL solution, and then add 8.44mL of H2PtCl6, 0.2053g of K2RuCl5·H2O and 0.6773g of (NH4)Mo7O in sequence. 24 ·4H2O, stir and mix evenly, adsorb at 40℃ for 6h, then centrifuge and dry to obtain resin adsorbed with metal ions;
[0080] (3) Disperse the resin adsorbed with metal ions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 0.6:1. Then add an equal volume of pH=10NH3·H2O solution and stir at 60℃ for 10h to hydrolyze. The hydrolysate coats the resin adsorbed with metal ions.
[0081] (4) The product obtained in step (3) is heat-treated in a mixed gas of hydrogen and nitrogen, wherein the volume content of hydrogen in the mixed gas is 10%, the heat treatment temperature is 900℃, and the time is 6.5h.
[0082] (5) The heat-treated material is immersed in 2M NaOH solution and hydrothermally treated at 80℃ for 60h. Then it is acid washed with 1M HNO3 solution at 60℃ for 2h. After filtration, washing, drying and grinding, the desired catalyst is obtained.
[0083] The performance test results of the catalyst obtained in Example 4 are as follows: Figure 4 As shown, 4-1 is the XRD detection result, 4-2 is the LSV detection result, 4-3 is the CO dissolution detection result, 4-4 is the single cell polarization curve and power density curve, and 4-5 is the TEM image and mapping image.
[0084] The test results showed that LSV activity was higher than 2.5 mA cm⁻¹. -2 (LSV is mainly determined by the hydroxide activity, with 2.5 mA cm⁻¹) -2 For reference only, values above 2.5 mA cm -2 It exhibits good hydrogen hydration activity; the CO desorption peak apex position is similar to that of commercial PtRu (0.5V); the methanol oxidation onset potential of the PtRuMo / C catalyst is lower than that of the commercial JM PtRu catalyst, which is more conducive to methanol oxidation; I f / I b Approximately 4, higher than the PtRu of commercial JM. f / I b (1.46)(I f Forward anode peak current, I b : Reverse anode peak current. I f / I b It is commonly used to evaluate the resistance of electrocatalysts to poisoning during methanol oxidation; higher Ig f / I b The value shows good resistance to poisoning, because the higher the I value... f / I b The value indicates that less intermediate species accumulate during methanol oxidation, higher than the PtRu value of commercial JM. f / I b (1.46), Commercial JM's Pt / C of I f / I b (0.79)). TEM: Good dispersion; fuel cell performance is better than Pt / C.
[0085] Example 5: PtRuCo / C catalyst
[0086] A PtRuCo / C catalyst for fuel cells is prepared by the following steps:
[0087] (1) Take D301 resin and grind it through a 60-mesh sieve (0.25mm);
[0088] (2) Take 1g of ground D301 resin, add an appropriate amount of ultrapure water to prepare a 0.1g / mL solution, then add 5.37mL H2PtCl6, 0.1306g K2RuCl5·H2O and 0.1159g K3[Co(CN)3] in sequence, stir and mix evenly, adsorb at 40℃ for 6h, then centrifuge and dry to obtain resin adsorbed with metal ions;
[0089] (3) Disperse the resin adsorbed with metal ions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 0.6:1. Then add an equal volume of pH=10NH3·H2O solution and stir at 60℃ for 10h to hydrolyze. The hydrolysate coats the resin adsorbed with metal ions.
[0090] (4) The product obtained in step (3) is heat-treated in a mixed gas of hydrogen and nitrogen, wherein the volume content of hydrogen in the mixed gas is 10%, the heat treatment temperature is 900℃, and the time is 6.5h.
[0091] (5) The heat-treated material is immersed in 2M NaOH solution and hydrothermally treated at 80℃ for 60h. Then it is acid washed with 1M HNO3 solution at 60℃ for 2h. After filtration, washing, drying and grinding, the desired catalyst is obtained.
[0092] The performance test results of the catalyst obtained in Example 5 are as follows: Figure 5 As shown, 5-1 is the XRD detection result, 5-2 is the CO dissolution detection result, 5-3 is the single cell polarization curve and power density curve, and 5-4 is the TEM image and mapping image.
[0093] XRD: Synthetic PtRuCo / C alloy catalyst; HOR current density less than 2.5 mA cm⁻¹ -2 The CO desorption peak at 0.5V is similar to that of commercial PtRu (0.5V). The methanol oxidation onset potential of the PtRuCo / C catalyst is lower than that of commercial PtRu (lower than 0.5V, indicating strong resistance to CO poisoning); I f / I b Approximately 1.75. As can be seen from the fuel cell performance graph, the PtRuCo / C catalyst has a higher open-circuit voltage than JM-Pt / C, better mass transfer across the entire current range, and a higher peak power density. TEM: The catalyst is uniformly dispersed on the carbon support.
[0094] Example 6: PtFe / C catalyst
[0095] A PtFe / C catalyst for fuel cells is prepared by the following steps:
[0096] (1) Take D301 resin and grind it through a 60-mesh sieve (0.25mm);
[0097] (2) Take 1g of ground D301 resin, add an appropriate amount of ultrapure water to prepare a solution of 0.1g / mL, then add 5.6mL of H2PtCl6 and 0.18g of K3Fe(CN)6 in sequence, stir and mix evenly, adsorb at 60℃ for 8h, then centrifuge and dry to obtain resin adsorbed with metal ions.
[0098] (3) Disperse the resin adsorbed with metal ions in ethanol solvent, then add sodium silicate. The mass ratio of the added sodium silicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 0.6:1. Then add an equal volume of pH=10NH3·H2O solution and stir at 80℃ for 5h to hydrolyze. The hydrolysate coats the resin adsorbed with metal ions.
[0099] (4) The product obtained in step (3) is heat-treated in a mixed gas of hydrogen and nitrogen, wherein the volume content of hydrogen in the mixed gas is 10%, the heat treatment temperature is 900℃, and the time is 6h.
[0100] (5) The heat-treated material is immersed in 2M NaOH solution and hydrothermally treated at 80℃ for 50h. Then, it is filtered, washed, dried and ground to obtain the desired catalyst.
[0101] The performance test results of the catalyst obtained in Example 6 are as follows: Figure 6 As shown, 6-1 is the XRD detection result, 6-2 is the LSV detection result, 6-3 is the CO dissolution detection result, 6-4 is the single cell polarization curve and power density curve, and 6-5 is the TEM image and mapping image.
[0102] The XRD pattern shows that the characteristic peaks of the alloy catalyst shift to higher angles, indicating that Fe has entered the Pt lattice and formed an alloy. The LSV diagram shows E... 1 / 2 The ECSA is approximately 0.91V, which outperforms commercial Pt / C (0.895V) catalysts. Based on the CO dissolution peak, the ECSA is calculated to be 57.97m. 2 / g, ECSA than Pt / C (40wt.%, 10μg) (43.31m 2The larger / g value indicates that the catalyst has more catalytic centers and better activity during the catalytic process. Comparing the peak potentials of CO oxidation, the peak potential of CO oxidation on the PtFe catalyst surface (0.65V) is negatively shifted compared to JM-Pt / C (0.737V), indicating that CO adsorbed by the PtFe catalyst is more easily oxidized. TEM further analysis of the morphology and composition of the PtFe / C catalyst showed that the catalyst remained uniformly dispersed on the carbon support after high-temperature heat treatment at 900℃, and the elemental distribution image showed that Pt (purple) and Fe (red) were uniformly distributed throughout the particles. The fuel cell diagram shows that the performance of the PtFe / C catalyst is superior to that of commercial Pt / C.
[0103] Example 7: PtSnCo / C catalyst
[0104] A PtSnCo / C catalyst for fuel cells is prepared by the following steps:
[0105] (1) Take D301 resin and grind it through a 60-mesh sieve (0.25mm);
[0106] (2) Take 1g of ground D301 resin, add an appropriate amount of ultrapure water to prepare a 0.1g / mL solution, then add 4.37mL H2PtCl6, 0.141g K3[Co(CN)6] and 0.127g K2SnO3 in sequence, stir and mix evenly, adsorb at 40℃ for 6h, then centrifuge and dry to obtain resin adsorbed with metal ions;
[0107] (3) Disperse the resin adsorbed with metal ions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 0.6:1. Then add an equal volume of pH=10NH3·H2O solution and stir at 60℃ for 3h to hydrolyze. The hydrolysate coats the resin adsorbed with metal ions.
[0108] (4) The product obtained in step (3) is heat-treated in a mixture of hydrogen and nitrogen, wherein the volume content of hydrogen in the mixture is 5%, the heat treatment temperature is 800℃, and the time is 6.5h.
[0109] (5) The heat-treated material is immersed in 2M NaOH solution and hydrothermally treated at 80℃ for 60h. Then it is acid washed with 1M HNO3 solution at 60℃ for 2h. After filtration, washing, drying and grinding, the desired catalyst is obtained.
[0110] The performance test results of the catalyst obtained in Example 7 are as follows: Figure 7As shown, 7-1 is the XRD detection result, 7-2 is the LSV detection result, 7-3 is the CO dissolution detection result, and 7-4 is the TEM image and mapping image.
[0111] The XRD pattern confirms the successful preparation of a PtSnCo ternary alloy. The half-wave potential is similar to that of Pt / C, and the calculated ECSA based on the CO dissolution peak is 65.74 m. 2 / g, which is greater than that of the JM-Pt / C catalyst. At the same time, it can be seen that the CO peak position is negatively shifted relative to JM-Pt / C, indicating that CO adsorption and desorption are easier on the PtSnCo / C catalyst.
[0112] Example 8: PtCoAu / C catalyst
[0113] A PtCoAu / C catalyst for fuel cells is prepared by the following steps:
[0114] (1) Take D301 resin and grind it through a 60-mesh sieve (0.25mm);
[0115] (2) Take 1g of ground D301 resin, add an appropriate amount of ultrapure water to prepare a solution of 0.1g / mL, then add 4.92mL H2PtCl6, 0.159g K3[Co(CN)6] and 0.181g KAuCl6 in sequence, stir and mix evenly, adsorb at 40℃ for 6h, then centrifuge and dry to obtain resin adsorbed with metal ions;
[0116] (3) Disperse the resin adsorbed with metal ions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 0.6:1. Then add an equal volume of pH=10NH3·H2O solution and stir at 60℃ for 3h to hydrolyze. The hydrolysate coats the resin adsorbed with metal ions.
[0117] (4) The product obtained in step (3) is heat-treated in a mixture of hydrogen and nitrogen, wherein the volume content of hydrogen in the mixture is 5%, the heat treatment temperature is 800℃, and the time is 6.5h.
[0118] (5) The heat-treated material is immersed in 2M NaOH solution and hydrothermally treated at 80℃ for 60h. Then it is acid washed with 1M HNO3 solution at 60℃ for 2h. After filtration, washing, drying and grinding, the desired catalyst is obtained.
[0119] The performance test results of the catalyst obtained in Example 8 are as follows: Figure 8As shown, 8-1 is the XRD detection result, 8-2 is the LSV detection result, 8-3 is the CO dissolution detection result, and 8-4 is the TEM image and mapping image.
[0120] The XRD pattern shows partial reduction to form PtCoAu, with some Au diffraction peaks remaining, indicating that Au did not completely enter the Pt and Co lattice to form an alloy. The Et value obtained from the ORR polarization curve is also relevant. 1 / 2 The V is approximately 0.901, which outperforms commercial Pt / C (0.895 V) catalysts. The ECSA is calculated to be 57.70 m based on the CO dissolution peak. 2 / g, ECSA than Pt / C (40wt.%, 10μg) (43.31m 2 The larger / g) indicates that the catalyst has more catalytic centers and better activity during the catalytic process. Comparing the peak potentials of CO oxidation, the peak potential of CO oxidation on the PtCoAu catalyst surface is negatively shifted compared to JM-Pt / C (0.737V), indicating that CO adsorbed by the PtCoAu catalyst is more easily oxidized.
[0121] Example 9: PtPdAu / C catalyst
[0122] A PtPdAu / C catalyst for fuel cells is prepared by the following steps:
[0123] (1) Take D301 resin and grind it through a 60-mesh sieve (0.25mm);
[0124] (2) Take 1g of ground D301 resin, add an appropriate amount of ultrapure water to prepare a 0.1g / mL solution, then add 5.62mL H2PtCl6, 0.218g K2PdCl6 and 0.207g KAuCl6 in sequence, stir and mix evenly, adsorb at 40℃ for 6h, then centrifuge and dry to obtain resin adsorbed with metal ions;
[0125] (3) Disperse the resin adsorbed with metal ions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 0.6:1. Then add an equal volume of pH=10NH3·H2O solution and stir at 60℃ for 10h to hydrolyze. The hydrolysate coats the resin adsorbed with metal ions.
[0126] (4) The product obtained in step (3) is heat-treated in a mixture of hydrogen and nitrogen, wherein the volume content of hydrogen in the mixture is 5%, the heat treatment temperature is 800℃, and the time is 6.5h.
[0127] (5) The heat-treated material is immersed in 2M NaOH solution and hydrothermally treated at 80℃ for 60h. Then it is acid washed with 1M HNO3 solution at 60℃ for 2h. After filtration, washing, drying and grinding, the desired catalyst is obtained.
[0128] The performance test results of the catalyst obtained in Example 9 are as follows: Figure 9 As shown, 9-1 is the XRD detection result, 9-2 is the LSV detection result, 9-3 is the CO dissolution detection result, and 9-4 is the TEM image and mapping image.
[0129] The XRD pattern shows that a PtPdAu / C alloy catalyst was synthesized, but the main peak exhibits significant splitting. This is likely because increasing temperature affects the diffusion rate of Pd and Au atoms into Pt, leading to segregation and alloy impurity. The ET value was obtained from the ORR polarization curve. 1 / 2 The V is approximately 0.877, and its performance is close to that of commercial Pt / C (0.895 V) catalysts. The ECSA is calculated to be 66.21 m based on the CO dissolution peak. 2 / g, ECSA than Pt / C (40wt.%, 10μg) (43.31m 2 The larger / g indicates that the catalyst has more catalytic centers and better activity during the catalytic process. Comparing the peak potentials of CO oxidation, the peak potential of CO oxidation on the surface of the PtPdAu / C catalyst (0.644V) is negatively shifted compared to JM-Pt / C (0.737V), indicating that CO adsorbed by the PtPdAu / C catalyst is more easily oxidized.
[0130] Example 10: PtPd / C catalyst
[0131] A PtPd / C catalyst for fuel cells is prepared by the following steps:
[0132] (1) Take D301 resin and grind it through a 60-mesh sieve (0.25mm);
[0133] (2) Take 1g of ground D301 resin, add an appropriate amount of ultrapure water to prepare a solution of 0.1g / mL, then add 6.57mL H2PtCl6 and 0.254g K2PdCl6 in sequence, stir and mix evenly, adsorb at 40℃ for 6h, then centrifuge and dry to obtain resin adsorbed with metal ions.
[0134] (3) Disperse the resin adsorbed with metal ions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 0.6:1. Then add an equal volume of pH=10NH3·H2O solution and stir at 60℃ for 10h to hydrolyze. The hydrolysate coats the resin adsorbed with metal ions.
[0135] (4) The product obtained in step (3) is heat-treated in a mixed gas of hydrogen and nitrogen, wherein the volume content of hydrogen in the mixed gas is 5%, the heat treatment temperature is 900℃, and the time is 6.5h.
[0136] (5) The heat-treated material is immersed in 2M NaOH solution and hydrothermally treated at 80℃ for 60h. Then it is acid washed with 1M HNO3 solution at 60℃ for 2h. After filtration, washing, drying and grinding, the desired catalyst is obtained.
[0137] The performance test results of the catalyst obtained in Example 10 are as follows: Figure 10 As shown, 10-1 is the XRD detection result, 10-2 is the LSV detection result, 10-3 is the CO dissolution detection result, and 10-4 is the TEM image and mapping image.
[0138] The XRD pattern of PtPd shows that the characteristic peaks of the alloy catalyst shift to higher angles, indicating that Pd has entered the Pt lattice and formed an alloy. The LSV diagram shows E... 1 / 2 With an ECSA of approximately 0.90 V, it outperforms commercial Pt / C (0.895 V) catalysts, and the calculated ECSA is 54.96 m based on the CO dissolution peak. 2 / g, higher than Pt / C (40wt.%, 10μg) (43.31m) 2 The presence of more catalytic centers ( / g) in the PtPd / C catalyst indicates that it has better activity during the catalytic process. Comparing the peak potentials of CO oxidation, the peak potential of CO oxidation on the PtPd / C catalyst surface (0.655V) is negatively shifted compared to JM-Pt / C (0.737V), indicating that CO adsorbed by the PtPd / C catalyst is more easily oxidized.
[0139] Example 11: PtRuFe / C catalyst
[0140] A PtRuFe / C catalyst for fuel cells is prepared by the following steps:
[0141] (1) Take D301 resin and grind it through a 60-mesh sieve (0.25mm);
[0142] (2) Take 1g of ground D301 resin, add an appropriate amount of ultrapure water to prepare a 0.1g / mL solution, then add 6.56mL H2PtCl6, 0.18g K3Fe(CN)6 and 0.1596g K2RuCl5·H2O in sequence, stir and mix evenly, adsorb at 60℃ for 10h, then centrifuge and dry to obtain resin adsorbed with metal ions;
[0143] (3) Disperse the resin adsorbed with metal ions in ethanol solvent, then add sodium silicate. The mass ratio of the added sodium silicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 1:1. Then add an equal volume of 0.1M NaOH solution and stir and hydrolyze at room temperature for 8 hours. The hydrolysate coats the resin adsorbed with metal ions.
[0144] (4) The product obtained in step (3) is heat-treated in a mixed gas of hydrogen and argon, wherein the volume content of hydrogen in the mixed gas is 10%, the heat treatment temperature is 800℃, and the time is 7h.
[0145] (5) Immerse the heat-treated material in a mixed solution of glacial acetic acid, hydrofluoric acid (40%), and ammonium chloride (40%) (V 冰醋酸 V 氢氟酸 V 氟化铵 =4:1:7,), stirred at room temperature for 6 hours, then filtered, washed, dried and ground to obtain the desired catalyst.
[0146] The performance test results of the catalyst obtained in Example 11 are as follows: Figure 11 As shown, 11-1 is the XRD detection result, 11-2 is the CO dissolution detection result, 11-3 is the single cell polarization curve and power density curve, and 11-4 is the TEM image and mapping image.
[0147] XRD patterns confirm the successful preparation of the PtRuFe / C alloy catalyst. The PtRuFe / C catalyst exhibits a lower methanol oxidation onset potential (0.4 V) than the PtRu catalyst (0.5 V), which is more favorable for methanol oxidation. f / I b Approximately 3, higher than the PtRu of commercial JM. f / I b (1.46). The fuel cell diagram shows that the PtRuFe / C catalyst outperforms the commercial Pt / C catalyst.
[0148] Example 12: PtRuMoNi / C catalyst
[0149] A PtRuMoNi / C catalyst for fuel cells is prepared by the following steps:
[0150] (1) Take D301 resin and grind it through a 60-mesh sieve (0.25mm);
[0151] (2) Take 1g of ground D301 resin, add an appropriate amount of ultrapure water to prepare a 0.1g / mL solution, and then add 4.22mL of H2PtCl6, 0.1026g of K2RuCl5·H2O, and 0.3387g of (NH4)Mo7O in sequence. 24 Mix 0.071g K2Ni(CN)4 with water, stir until homogeneous, adsorb at 40℃ for 6h, then centrifuge and dry to obtain resin adsorbed with metal ions.
[0152] (3) Disperse the resin adsorbed with metal ions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 0.6:1. Then add an equal volume of pH=10NH3·H2O solution and stir at 60℃ for 10h to hydrolyze. The hydrolysate coats the resin adsorbed with metal ions.
[0153] (4) The product obtained in step (3) is heat-treated in a mixed gas of hydrogen and nitrogen, wherein the volume content of hydrogen in the mixed gas is 10%, the heat treatment temperature is 900℃, and the time is 6.5h.
[0154] (5) The heat-treated material is immersed in 2M NaOH solution and hydrothermally treated at 80℃ for 60h. Then it is acid washed with 1M HNO3 solution at 60℃ for 2h. After filtration, washing, drying and grinding, the desired catalyst is obtained.
[0155] The performance test results of the catalyst obtained in Example 12 are as follows: Figure 12 As shown, 12-1 is the XRD detection result, 12-2 is the LSV detection result, 12-3 is the CO dissolution detection result, and 12-4 is the TEM image and mapping image.
[0156] XRD: Synthesized PtRuMoNi / C alloy, LSV activity greater than 2.5 mA cm⁻¹ -2 The CO desorption peak position is about 0.4V, which is smaller than that of commercial PtRu catalyst (0.5V). The peak position of PtRuMoNi / C catalyst is also lower than that of commercial PtRu. The If / Ib ratio is about 3, which is higher than that of commercial JM PtRu catalyst (1.46).
[0157] Example 13: PtRuNi / C catalyst
[0158] A PtRuNi / C catalyst for fuel cells is prepared by the following steps:
[0159] (1) Take D301 resin and grind it through a 60-mesh sieve (0.25mm);
[0160] (2) Take 1g of ground D301 resin, add an appropriate amount of ultrapure water to prepare a 0.1g / mL solution, then add 7.18mL H2PtCl6, 0.1796g K2RuCl5·H2O and 0.1242g K2Ni(CN)4 in sequence, stir and mix evenly, adsorb at 40℃ for 6h, then centrifuge and dry to obtain resin adsorbed with metal ions;
[0161] (3) Disperse the resin adsorbed with metal ions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 0.6:1. Then add an equal volume of pH=10NH3·H2O solution and stir at 60℃ for 10h to hydrolyze. The hydrolysate coats the resin adsorbed with metal ions.
[0162] (4) The product obtained in step (3) is heat-treated in a mixed gas of hydrogen and nitrogen, wherein the volume content of hydrogen in the mixed gas is 10%, the heat treatment temperature is 900℃, and the time is 6.5h.
[0163] (5) The heat-treated material is immersed in 2M NaOH solution and hydrothermally treated at 80℃ for 60h. Then it is acid washed with 1M HNO3 solution at 60℃ for 2h. After filtration, washing, drying and grinding, the desired catalyst is obtained.
[0164] The performance test results of the catalyst obtained in Example 13 are as follows: Figure 13 As shown, 13-1 is the XRD detection result, 13-2 is the LSV detection result, 13-3 is the CO dissolution detection result, and 13-4 is the TEM image and mapping image.
[0165] XRD results showed that a PtRuNi / C alloy was synthesized, with a HOR current density of less than 2.5 mA cm⁻¹. -2 The CO desorption peak position is similar to that of the commercial JM PtRu catalyst, and the peak position of the PtRuNi / C catalyst is higher than that of the commercial PtRu; the If / Ib ratio is about 1, which is lower than that of the commercial PtRu catalyst (1.46).
[0166] Example 14: PtMo / C catalyst
[0167] A PtMo / C catalyst for fuel cells is prepared by the following steps:
[0168] (1) Take D301 resin and grind it through a 60-mesh sieve (0.25mm);
[0169] (2) Take 1g of ground D301 resin, add an appropriate amount of ultrapure water to prepare a 0.1g / mL solution, and then add 4.92mL of H2PtCl6 and 0.3951g of (NH4)Mo7O in sequence. 24 Stir and mix evenly, adsorb at 40℃ for 6 hours, then centrifuge and dry to obtain resin adsorbed with metal ions.
[0170] (3) Disperse the resin adsorbed with metal ions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 0.6:1. Then add an equal volume of pH=10NH3·H2O solution and stir at 60℃ for 10h to hydrolyze. The hydrolysate coats the resin adsorbed with metal ions.
[0171] (4) The product obtained in step (3) is heat-treated in a mixed gas of hydrogen and nitrogen, wherein the volume content of hydrogen in the mixed gas is 10%, the heat treatment temperature is 900℃, and the time is 6.5h.
[0172] (5) The heat-treated material is immersed in 2M NaOH solution and hydrothermally treated at 80℃ for 60h. Then it is acid-washed with 1M HNO3 solution at 80℃ for 2h. After filtration, washing, drying and grinding, the desired catalyst is obtained.
[0173] The performance test results of the catalyst obtained in Example 14 are as follows: Figure 14 As shown, 14-1 is the XRD detection result, 14-2 is the LSV detection result, 14-3 is the CO dissolution detection result, and 14-4 is the TEM image and mapping image.
[0174] The XRD pattern confirmed the successful synthesis of the PtMo / C alloy catalyst, with an HOR current density of less than 2.5 mA cm⁻¹. -2 The onset position of the CO desorption peak is similar to that of the commercial JM PtRu catalyst, but the onset potential of the PtRu catalyst is higher than that of the commercial PtRu; the If / Ib ratio is about 0.75, which is lower than that of the commercial JM PtRu catalyst (1.46).
[0175] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a catalyst for fuel cells, characterized in that, Includes the following steps: (1) The Pt precursor and the soluble metal precursor are co-dissolved in water, and then an anion exchange resin is added for adsorption. After separation and drying, the resin adsorbed with metal ions is obtained. (2) The resin adsorbed with metal ions is dispersed in a solvent, and then a silicon-containing compound hydrolyzed under acidic or alkaline conditions is added. Then, an acid solution or an alkaline solution is added for hydrolysis, and the hydrolysate coats the resin adsorbed with metal ions. (3) The material obtained in step (2) is heat-treated in a reducing atmosphere, and then post-treated, washed, and dried to obtain the final product; wherein the reducing atmosphere is a mixture of hydrogen and argon or hydrogen and nitrogen, and the volume content of hydrogen in the mixture is 5%~40%; the heat treatment temperature is 700~900℃, and the heat treatment time is 6~8h; the post-treatment involves immersing the heat-treated material in a sodium hydroxide solution with a concentration of 1~3M. The heat-treated material is soaked in a solution at 80-120℃ for 50-70 hours, followed by acid washing with a 1-3M nitric acid solution at 50-70℃ for 2 hours; or, the heat-treated material is immersed in a 10% hydrofluoric acid solution and stirred at room temperature for 5-12 hours; or, the heat-treated material is immersed in a mixed solution of glacial acetic acid, hydrofluoric acid, and ammonium fluoride and stirred at room temperature for 1-8 hours, wherein the volume ratio of glacial acetic acid, hydrofluoric acid, and ammonium fluoride in the mixed solution is 4:1:
7. The catalyst used in the fuel cell is an ordered intermetallic compound.
2. The method for preparing a catalyst for a fuel cell according to claim 1, characterized in that: The anion exchange resin has a particle size of less than 0.25 mm.
3. The method for preparing a catalyst for fuel cells according to claim 1, characterized in that: In step (1), the molar ratio of Pt precursor to soluble metal precursor is 1:1 to 5:1; the Pt precursor is chloroplatinic acid, potassium chloroplatinate, or potassium chloroplatinate; the soluble metal precursor is at least one of sodium cobalt cyanide, potassium cobalt cyanide, ammonium hexachlororuthenate, potassium pentachlororuthenate, potassium hexacyanoruthenate, ammonium molybdate, sodium molybdate, chloroauric acid, sodium ferrocyanide, potassium ferrocyanide, potassium nickel cyanide, potassium hexacyanide nickelate, potassium chloropalladium, sodium chloropalladium, ammonium chloropalladium, sodium tungstate, ammonium tungstate, sodium stannate, and potassium stannate.
4. The method for preparing a catalyst for a fuel cell according to claim 1, characterized in that: In step (1), the adsorption temperature is 15~80℃ and the adsorption time is 4~12h.
5. The method for preparing a catalyst for a fuel cell according to claim 1, characterized in that: The mass ratio of the silicon-containing compound (based on silicon dioxide) to the resin adsorbed with metal ions is 1:2 to 2:1; the silicon-containing compound is a silicate, methyl orthosilicate, ethyl orthosilicate, or 3-aminopropyltriethoxysilane.
6. The method for preparing a catalyst for a fuel cell according to claim 1, characterized in that: The acid solution in step (2) is a hydrochloric acid solution with pH=1~3, and the alkaline solution is an ammonia solution with pH=9~11; the hydrolysis temperature is 15~80℃, and the hydrolysis time is 3~10h.
7. A fuel cell catalyst prepared by any one of claims 1 to 6.
8. The catalyst for fuel cells according to claim 7, characterized in that: The catalysts used in the fuel cells are PtCo / C, PtFe / C, PtNi / C, PtPd / C, PtCoAu / C, PtPdAu / C, PtRu / C, PtRuCo / C, PtSnCo / C, Pt-MoC / C, and PtRu-MoC / C.
9. The application of the fuel cell catalyst as described in claim 7 or 8 as a fuel cell cathode oxygen reduction catalyst, a fuel cell hydroxide catalyst, or a methanol fuel cell anode catalyst.
Citation Information
Patent Citations
Preparation method of carbonized Pd (palladium)-carrying hollow anion exchange resin microsphere H2O2 (hydrogen peroxide) electroreduction catalyst
CN104084196A
Silicon dioxide-protected carbon-based catalyst as well as preparation method and application thereof
CN109675603A